Cambridge IELTS 14: Academic with answers - Cambridge IELTS (Sonipat; Kundli Cambridge University Press; Rajkamal Electric Press, 2021)
Authentic examination papers from Cambridge Assessment English provide perfect practice because they are EXACTLY like the real test. IELTS 14 Academic Student's Book with Answers with Audio gives students the perfect opportunity to familiarise themselves with IELTS and practise examination techniques using authentic test material. It provides an explanation of the scoring system used by Cambridge Assessment English. A comprehensive section of answers and audio scripts makes the material ideal for students working partly or entirely on their own.
Keywords: English Grammar